Reflecții pe marginea unor recenzii scrise de gazetarul Vasile Avram - Gabriel HASMAȚUCHI (Eon)
Through this article, we intended to bring to the attention of the public only a small, but, nevertheless, conclusive part of the contribution of the publicist Vasile Avram (1940-2002). The analysis focuses on 25 book reviews published by the journalist in Transilvania journal between the years 1977 and 1989 under the “Mișcarea literară” column. This selection gives us the possibility to focus on a certain sub-category belonging to the opinion journalism that Vasile Avram often opted for, to aesthetically guide the targeted audience. We consider these critical texts sufficient to illustrate that the journalist had the rare quality of a critic of good taste.